Status of an indigenous agroforestry system: A case study in Kumaun Himalaya, India - PARIHAAR, R S; BARGALI, KIRAN; BARGALI, S S (The Indian Journal of Agricultural Sciences, 2015)
The agro-forestry system is one of the best known indigenous practices for livelihood and sustainable development. In the present study a village Semalkhaliya (Ramnagar block) situated in bhabar belt of Kumaun Himalaya was analyzed with the objective to assess the indigenous agroforestry system with energy and economic efficiency of the landscape. This village includes 110 families with a human population of 631. Simultaneous agroforestry system was the main land use system being operated in the village. A total of fifteen tree species and twenty two crop species were reported from the study area. Among tree component, Mangifera indica, Tectona grandis and Populas sp were the most dominant species. The major cereals grown by the farmers were Triticum aestivum and Oryza sativa. Most of the surplus food was stored by the villagers for their use and rest is sold for cash. Besides food, the tree species grown in agroforestry based system were used for multipurpose such as fuel, fodder, medicine etc. Homegarden is another land use system which was commonly used by the farmers. In this system seasonal vegetable crops were grown with mixed plantation of fodder and fruit trees. In agroforestry system annual energy input was 81 905 MJ/ha and in home garden annual energy input was 53 913 MJ/ha. In terms of money, highest per ha annual productivity or income was greater in agriculture followed by the home gardens.